EXCHANGE RATE VOLATILITY AND SECTORAL EXPORTS: EMPIRICAL EVIDENCE FROM TWELVE E.U. MEMBER COUNTRIES (1973–2004) - Serenis, Dimitrios; Serenis, Paul (Journal of European Economy, 2017)
Abstract This paper examines potential effect of exchange rate volatility for a set of twelve E.U. member countries (Austria, Denmark, Finland, France, Greece, Ireland, Italy, The Netherlands, Spain, Sweden, Portugal and The U.K.) for sectoral exports of agricultural products during the period of 1973-2004. After critically reviewing the empirical literature we are able to conclude that empirical researchers often examine the hypothesis that exchange rate volatility is a major source of risk. As a result it is often claimed by some researchers that exchange rate volatility causes individual producers to switch their production from foreign to domestic markets where there is less risk. This switch will therefore cause a reduction in the overall level of trade. The review of the literature has identified mixed results with regard to the effects of exchange rate volatility and its potential effects on the level of trade. Therefore the ranges of expected relationships are: a negative relationship, a positive relationship, an indeterminate or no relationship between exchange rate volatility and the level of exports. We therefore examine the effects of exchange rate volatility by utilizing a measure of the standard deviation of the moving average of the logarithm of real exchange rate as a measure of exchange rate volatility and by adopting a conceptual framework of the imperfect substitution reduced form export quantity model similar to that of Arize. Overall our results have proved to be consistent with our past examinations which for the main part did not estimate any overall significant sectoral effects from volatility to exports with a few notable exceptions. Out of the fourteen sample countries examined in this study for only two the exchange rate volatility coefficient proved to be significant leaving the remaining countries with an insignificant relationship.